Development and validation of a five-year cardiovascular risk assessment tool for Asian adults aged 75 years and older - Meng-Chen Hsu; Yu-Hua Fu; Chi-Chuan Wang; Chau-Chung Wu; Fang-Ju Lin (BMC Geriatrics)
Abstract Background To identify cardiovascular (CV) risk factors in Asian elderly aged 75 years and older and subsequently develop and validate a sex-specific five-year CV risk assessment tool for this population. Methods This study included 12,174 patients aged ≥ 75 years without a prior history of cardiovascular disease at a single hospital in Taiwan. Electronic health records were linked to the National Health Insurance Research Database and the National Death Registry to ensure comprehensive health information. Eligible patients were randomly divided into derivation (80%) and validation (20%) cohorts. A sex-specific CV risk assessment tool was developed to predict major adverse cardiovascular events (MACE) using Cox regression modeling. Results During a median follow-up period of 8.6 years for men and 8.5 years for women in the derivation cohort, MACE occurred in 3.62% of men and 3.02% of women. Predictors for men comprised advanced age, smoking, non-HDL-C levels > 160 mg/dL, metastatic cancer, and aspirin usage. Predictors for women included advanced age, smoking, atrial fibrillation, cancer, dementia, osteoarthritis, systemic lupus erythematosus, use of antihypertensives, and use of oral anticoagulants. In the validation cohort, the sex-specific risk assessment tool demonstrated fair discriminative power (AUC: men, 0.64; women, 0.68). Model calibration demonstrated good performance for women but was less optimal for men. Conclusions This sex-specific CV risk assessment tool shows fair discriminative capability in estimating risk of cardiovascular disease among elderly Asians, potentially enabling targeted interventions in this vulnerable population.